Awareness and Frequency of Encounter With Subjects With Antiphospholipid Syndrome by Medical Practitioners in Tertiary and Some Other Health Institutions in Southeast Nigeria - Celestine C Okwara; Kingsley E Ekwuazi; Michael Abonyi; Fintan Ekochin; Winifred Adiri; Ijeoma Onwuchekwa; Henry Nwankwo; Ngozi Ekeigwe; Thomas Nnaji; Gladys Ozoh (International Journal of Medicine and Health Development)
Background: Antiphospholipid syndrome (APS) is an autoimmune multisystem disorder. There has been a limited number of reported cases from Nigeria.